Diurnal variation in baseline heart rate of anencephalic fetuses - MURO, MASAMI; SHONO, HIDEAKI; ITO, YUJI; SUGIMORI, HAJIME (Psychiatry and clinical neurosciences, 1998)
The diurnal change in baseline fetal heart rate (FHR) of four anencephalic fetuses at 20, 23, 24 and 30 weeks of gestation were examined. The mean baseline FHR in 00.00–06.00 h, 06.00–12.00 h, 12.00–18.00 h and 18.00–24.00 h were compared by one‐factor ANOVA and Scheffe's test in each case. The diurnal variations in baseline FHR were recognized in all subjects (P < 0.01). In 3/4 subjects, the lowest values were at 00.00–06.00 h. The diurnal variation in baseline FHR might be caused by maternal factors because it was present even in the anencephalic fetuses that had no central nervous system having the oscillators of the circadian rhythm.